The Collocations of the English Words Heart and Mind: Similarities and Differences - Nadia Ananda Herianto (Indonesian Journal of English Language Studies (IJELS), 2016)
Understanding collocations is essential to interpret meanings. This study aims to analyze the similarities and differences between the collocations of the English words heart and mind. About 99 data were taken from Corpus of Contemporary American English. The collocations were categorized based on the grammatical patterns. Then, the lexical meaning of each collocation was analyzed based on the context. The collocation patterns of the words heart and mind are almost similar. Seven categories of the collocations of the word heart include heart + noun (23.24%), heart + verb (20.20%), preposition + heart (16.16%), heart of + noun (15.15%), verb + heart (12.12%), other phrases (8.08%) and adjective + heart (5.05%). Meanwhile, seven categories of the collocation of the word mind include other phrases (33.33%), preposition + mind (30.30%), verb + mind (11.11%), noun + of mind (10.10%), adjective + mind (8.08%), mind + verb (6.06%) and mind + noun (1.01%). Collocations in the form of phrases tend to have idiomatic meanings. However, there is no clear relationship between the collocation patterns and meanings of both words.